William Bolts and his contributory role in the history of printing and publication of newspapers in Bengal, as well as in India. - Ms. Monamie Mukherjee., Mr. Biplab Kumar Chandra (Journal of Daoist Studies, 2026)
Though we all come through the name of James Augustus Hicky whenever we discuss the history of printing press of Calcutta, particularly his efforts in publishing the first regular newspaper in Calcutta, India in 1780 called ‘Bengal Gazette’, yet we should not forget to discuss that it was twelve years before Hicky that William Bolts was the first to take a huge leap towards establishing one. In fact, he was the first to propose to set up a printing press at Calcutta, and introduced a handwritten newspaper in Bengali in 1768. Once being himself an employee of the British East India Company, he showed the courage to write about the truth, of the oppressive misrules of the company. This newspaper obviously could not exist for long; Bolts’ affixation of a notice on the door of the Council House announcing his intention to bring out a newspaper created much uproar at the time. But his intention was not approved by the East India Company and he was ordered to quit India for “having endeavoured to utter an odium upon the administration and promote faction and discontentment”. [1] Bolts’ contribution in this part of history cannot be undermined, as he was truly a strong, influential character of his age and time.